1993
DOI: 10.1070/pu1993v036n05abeh002185
|View full text |Cite
|
Sign up to set email alerts
|

Report on the Third International Symposium on Ball Lightning

Abstract: The KLY hypersatellite spectrum of gaseous AI has been measured in photon excitation with a plane crystal Bragg spectrometer. The experimental energy of KCY; line is obtained. The result is in good agreement with available theoretical calculations. The K shell double photoionization cross-se.ction is estimated from the measured hypersatellite intensity and it is compared with existing theoretical calculations based on the shake theory and correlated wave functions. h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Experiments of this kind are also motivated by the observation of 1-s green fireballs in submarine batteries, probably related to electrode erosion in accidental short circuiting. Dijkhuis [62], performing experiments with a submarine battery and 150-kA currents, produced and filmed fireballs with a diameter of 10 cm and a lifetime of about 1 s. He suggested that the phenomenon is due to some kind of quantummechanical exchange force. More recently, Shavanov [63] obtained reproducible, luminous globular formations (about 10 cm in diameter, lasting up to 1 s) that appear in erosive discharges having typical BL colors.…”
Section: Artificial Ball Lightningmentioning
confidence: 99%
“…Experiments of this kind are also motivated by the observation of 1-s green fireballs in submarine batteries, probably related to electrode erosion in accidental short circuiting. Dijkhuis [62], performing experiments with a submarine battery and 150-kA currents, produced and filmed fireballs with a diameter of 10 cm and a lifetime of about 1 s. He suggested that the phenomenon is due to some kind of quantummechanical exchange force. More recently, Shavanov [63] obtained reproducible, luminous globular formations (about 10 cm in diameter, lasting up to 1 s) that appear in erosive discharges having typical BL colors.…”
Section: Artificial Ball Lightningmentioning
confidence: 99%